An Analysis Of Financial Ratios: The Case Of Corporate Waqf In Malaysia - Khairil Faizal Khairi; Nur Hidayah Laili; Mohamad Yazis Ali Basah; Muhammad Ridhwan Ab. Aziz; Hisham Sabri; Mohammad Noorizzuddin Nooh (Wulfenia Journal, 2024)
Volume: 21 No: 5 (page: 80-94)